Developing Connectivism Learning in Social Learning Platform Using Addie Instructional Design Model - Taufik Ikhsan Slamet; Dedi Kuswandi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
The aim of this study is to develop connectivism learning model that fits to social learning approach by using ADDIE instructional design. This model answers the need of learning model which can be implemented in social learning platform or in networked environment for general. To develop the model, ADDIE instructional design is used as phases of development process. This process involves analyze, design, development, implementation, and evaluation. This approach is considered as the most general model to design instruction, which can be implemented in varried of purposes. The participants of this study were 77 students of Educational Technology department of State University of Malang studying photography course. The quantitave analysis data of quesionnaire indicated that the Connectivism model was found to be adaptive and acceptable by the participants. The model received moderately positive acceptance from participants, and able to encourage collaborative activites through instructional process. The participants tend to be more confident to open the discussion or to share information and explore argumentation or suggestion. The process engaged the students to perform problem solving skills and collaborative work, which these performaces were not found on direct instruction in the classrom. Keywords: Connectivism model, ADDIE, Contribution Index (CI), Content Richness (CRs)